SUN-733 Analysis of Divergent Long Noncoding RNAs in Estrogen-Regulated Transcription - Lee, Debra (J Endocr Soc, 2020)
The role of long noncoding RNAs (lncRNAs) in cancer biology are just beginning to be elucidated and recent studies have shown that they could be therapeutic targets. In a previous study, combining powerful techniques, Global Run-On sequencing (GRO-seq) and subcellular fractionation RNA-seq in breast cancer cells identified a large number of estrogen-regulated unannotated long noncoding RNAs. Analysis of gene expression data from hundreds of samples representing 13 different tissue types including both cancer and normal tissue, revealed that many lncRNAs are differentially expressed in various cancers. Furthermore, a large number of lncRNAs are divergent transcripts and show distinct expression patterns across molecular subtypes of cancer. In functional assays, knockdown of selected lncRNA, such as lncRNA67, inhibits the growth of breast cancer cells. Amplified expression of lncRNA67 in luminal-subtype of breast cancer correlates with clinical outcome. LncRNA67 has now been fully annotated (transcription start and stop site, 5’ cap, polyA tail, and exon/intron structure), and cloned. Our preliminary molecular analyses indicate that lncRNA67 plays a critical role in ER-dependent and -independent pathways. Collectively, our results suggest that lncRNAs are an integral component of cancer biology.